La documentation des peintures murales de la Chapelle des fresques de Villeneuve-lès Avignon - Marie Feillou (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The documentation led for the conservation restauration of the mural paintings of the Chaterhouse of Villeneuve lès Avignon is linked with the constitution of a data base based on the 3D representation of the painted interior’s chapel. Thus the integration and spatialisation of the documentation’s datas in this database engender the wondering about documentation tools and the establishment of a work’s methodology based on new digital technology’s.